2019
DOI: 10.4178/epih.e2019027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cancer prevention education program on elementary school students’ knowledge, attitude, self-efficacy, and intentions in South Korea

Abstract: OBJECTIVES: Most children and adolescents have low levels of cancer knowledge and awareness, and infrequently engage in preventive behaviors. This study examined the effects of a short classroom-based intervention for cancer prevention on knowledge, attitude toward cancer preventability, self-efficacy, and behavioral intentions of fifth-grade elementary school students.METHODS: The study was based on a pre-post-follow-up, 2-group, quasi-experimental design. Participants in the intervention group attended two 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This was attributed to the ability of short-term interventions to change one’s knowledge but not necessarily the social cognitive factors that would reflect in a sustained behaviour change. Such sustained behaviour changes would take long-term interventions involving several booster sessions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to the ability of short-term interventions to change one’s knowledge but not necessarily the social cognitive factors that would reflect in a sustained behaviour change. Such sustained behaviour changes would take long-term interventions involving several booster sessions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41 - 43 Other countries have developed and implemented successful instructor-led programs designed to reach adolescents. 10 , 44 - 46 For example, Cancer, Educate to Prevent (CEP) was successful and effective in both educating high school students on cancer prevention and preparing their biology teachers to utilize this curriculum in schools. 10 , 45 The Australian-based Sun Smart program incorporates technological interventions such as a media campaign, two mobile video games, and a mobile app as a component of a robust set of educational materials.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Other countries have developed and implemented successful instructor-led programs designed to reach adolescents. 10,[44][45][46] For example, Cancer, Educate to Prevent (CEP) was successful and effective in both educating high school students on cancer prevention and preparing their biology teachers to utilize this curriculum in schools.…”
Section: Educational Programs and Technologymentioning
confidence: 99%
“…However, while education programs can result in short-term knowledge improvements in cancer prevention, their long-term effects on behavioral intentions and practices require further study [13]. Thus, it has been suggested that such programs incorporate education booster sessions to assess and maintain long-term changes in cancer prevention behaviors [27]. In other countries like New Zealand, researchers have issued recommendations for the government to provide adequate resources as part of a broader evidence-based public health program to increase cancer literacy and support preventive behavior changes in the general population [28].…”
Section: Discussionmentioning
confidence: 99%